(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The study assessed the impact of library websites and automated library resources on service delivery in academic libraries in Akwa Ibom State. Two research questions and two research hypotheses were formulated to guide the study. The research design adopted for the study was descriptive research design. The sample size of 45 Librarians from 3 academic libraries in the study area involved in the study. A structural questionnaire tagged Library Websites and Automated Library Resources Questionnaire (LWALRQ) was designed by the researchers and used for data collection. The instrument was vetted by two experts in Department of Education Foundation University of Uyo based on the variables under study. The data collected was analyzed using mean statistics to answer research questions and t-test to test the hypotheses. The result reveals that a significant influence exist between each of the variables and service delivery in academic libraries in Akwa Ibom State. It concludes that library websites and automated library resources have significantly influenced library service delivery in academic libraries. Hence, it is recommended among other things that management of academic libraries in Akwa Ibom State should ensure they maintain the library websites for effective service delivery.